2017
DOI: 10.3390/ncrna3010013
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA MultiTool: A Software for Identifying Modified and Unmodified Human microRNA Using Mass Spectrometry

Abstract: microRNA (miRNA) are short endogenous non-coding RNA that play a crucial role in post-transcriptional gene regulation and have been implicated in the initiation and progression of 160+ human diseases. Excellent analytical methods have been developed for the measurement of miRNA by mass spectrometry. However, interpretation of mass spectrometric data has been an incapacitating bottleneck in miRNA identification. This study details the development of MicroRNA MultiTool, a software for the identification of miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The current technologies/techniques used for the study of nutrigenetics and nutrigenomics are shown in Table 1. The demand for determining genome, transcriptome, proteome, metabolome and mutation-specific profile characteristics has led to the implementation of several technologies, some of which are simple and inexpensive technologies, such as polymerase chain reaction (PCR)-based methods [7,11,12,13]. The more complex and costly technologies consist of microarray, Sanger sequencing and next generation sequencing (NGS), mass spectrometry (MS), and liquid chromatography coupled with mass spectrometry (LC–MS).…”
Section: Introductionmentioning
confidence: 99%
“…The current technologies/techniques used for the study of nutrigenetics and nutrigenomics are shown in Table 1. The demand for determining genome, transcriptome, proteome, metabolome and mutation-specific profile characteristics has led to the implementation of several technologies, some of which are simple and inexpensive technologies, such as polymerase chain reaction (PCR)-based methods [7,11,12,13]. The more complex and costly technologies consist of microarray, Sanger sequencing and next generation sequencing (NGS), mass spectrometry (MS), and liquid chromatography coupled with mass spectrometry (LC–MS).…”
Section: Introductionmentioning
confidence: 99%